2011
DOI: 10.1121/1.3632048
|View full text |Cite
|
Sign up to set email alerts
|

Cross-language specialization in phonetic processing: English and Hindi perception of /w/-/v/ speech and nonspeech

Abstract: This study examined the perceptual specialization for native-language speech sounds, by comparing native Hindi and English speakers in their perception of a graded set of English /w/-/v/ stimuli that varied in similarity to natural speech. The results demonstrated that language experience does not affect general auditory processes for these types of sounds; there were strong cross-language differences for speech stimuli, and none for stimuli that were nonspeech. However, the cross-language differences extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 24 publications
(33 reference statements)
2
12
0
Order By: Relevance
“…Santoro et al, 2014). Indeed, it may prove misguided to assume a privileged status for speech, or for there to be a categorical distinction between speech and other sounds (Iverson et al, 2011;Iverson et al, 2016;Rosen & Iverson, 2007).…”
Section: (B) Cortical (A)symmetries: Is Speech Comprehension Left-dommentioning
confidence: 99%
“…Santoro et al, 2014). Indeed, it may prove misguided to assume a privileged status for speech, or for there to be a categorical distinction between speech and other sounds (Iverson et al, 2011;Iverson et al, 2016;Rosen & Iverson, 2007).…”
Section: (B) Cortical (A)symmetries: Is Speech Comprehension Left-dommentioning
confidence: 99%
“…for stimuli that had spectral-temporal variation that was different enough from normal speech (Experiment 2). That being said, Experiment 2 adds to our previous examples (Iverson et al, 2011) of stimuli that are difficult to categorize phonemically, and sometimes not even sound like speech, but are affected by language experience.…”
Section: Discussionmentioning
confidence: 95%
“…This approach of exploring the territory between speech and non-speech was used by Iverson et al (2011) to examine the perception of English /w/-/v/ by English and Hindi speakers. We used a set of English /w/-/v/ continua that acoustically deconstructed the stimuli so that they varied in the degree that they sounded like speech or non-speech.…”
Section: Introductionmentioning
confidence: 99%
“…Hindi, however, does not contrast these speech sounds. It is unclear to what extent Hindi speakers of Indian English produce or perceive speech categories that resemble /v/ or /w/ found in English varieties spoken by speakers of American or British English Iverson, Wagner, Pinet, & Rosen, 2011). The lack of contrast between /v/ and /w/ in Hindi is reflected in Hindi orthography, in which the grapheme "व" represents a single Hindi speech sound /ʋ/, which is the closest match to English /v/ or /w/ (Ohala, 1999;Pierrehumbert & Nair, 1996;Sahgal & Agnihotri, 1988;Whitney, 1896).…”
Section: Status Of /V/ and /W/ In English Versus Hindimentioning
confidence: 99%
“…Because Hindi speakers produce this labiodental approximant /ʋ/ in Hindi, it is important to explore how they perceive English /v/ and /w/. Previous studies showed that Hindi speakers assimilated English /v/ and /w/ to the single Hindi labiodental approximant /ʋ/ (Iverson, Ekanayake, Hamann, Sennema, & Evans, 2008;Iverson et al, 2011). In line with the previous findings, our pilot data with eight Hindi speakers also showed that Hindi speakers assimilated 100 % of English /v/ and /w/ tokens to the single labiodental approximant /ʋ/ in Hindi.…”
Section: Status Of /V/ and /W/ In English Versus Hindimentioning
confidence: 99%